Pendirian Danantara dalam Revisi Undang-Undang Bumn: Implikasi terhadap Struktur Pengelolaan BUMN di Indonesia - Racmawati Eka , Amanda; Nachrawi, Gunawan (Neolectura, 2026)
The establishment of State-Owned Enterprises (SOEs) is a strategic effort to enhance national economic growth. To maximize their contribution, SOEs require governance that is independent, professional, and based on Good Corporate Governance principles. The government’s creation of Danantara aims to centralize SOE operations and separate them from regulatory functions. This study analyzes the impact of Danantara’s formation on SOE governance, focusing on the separation of regulatory and operational roles and its implications for investment and efficiency. Using a normative juridical approach, the research examines legal norms and frameworks related to SOE management. Findings show that the inclusion of Danantara in the revision of SOE Law No. 1 of 2025 significantly changes governance structures. Previously, the Ministry of SOEs and the Ministry of Finance handled both regulatory and operational duties; now, the Ministry acts solely as a regulator, while Danantara manages operational functions. This reform improves efficiency and investment coordination but poses challenges in redefining SOEs, excluding them from state finance status, and recognizing losses as corporate rather than state losses. These changes are crucial for future SOE governance and their strategic role in national economic development